Mongolia’s Regional Development : Selected Issues - World Bank (Washington, DC, 2021)
The objective of this policy note is to highlight key implementation issues and provide policy recommendations for promoting the Government's stated goal of achieving balanced regional development based on an analysis of: i) the evolving regional dynamics within Mongolia, ii) its current intergovernmental fiscal setup and iii) the lessons from international experience on regional development and economic growth. Although, regional development will have important implications for all sectors of the economy, this note includes a section on the impact of the mining sector on regional development in the country given its strategic importance in the long-term development of Mongolia. A detailed analysis of other sector-specific issues is beyond the scope of this policy note.